Development of a Network Security System with Mikrotik in SMK Muhammadiyah 2 Kuningan - Ainnul Yaqin; Firmansyah Firmansyah (Institute of Computer Science (IOCS), 2020)
Currently the internet is used and utilized in all fields of human life both in the economic, government, and even now the internet has been widely used in the world of education as a support in the learning process. One of the uses of the internet in learning is to look for subject matter in the form of articles, pictures and even videos. But not all things that are on the internet are good, there are a lot of negative content that needs to be filtered to prevent internet abuse by students, for example accessing graphic porn content, opening social media sites on Facebook, Instagram and even watching video shows on YouTube while learning takes place.The main purpose of this study is to control and prevent internet abuse by students at SMK Muhammadiyah 2 Kuningan by blocking sites that are not needed during learning and user management and bandwidth management with Router Mikrotik so that internet connections are stable. The results of the research carried out successfully implemented with the results, sites containing negative content were blocked, the internet connection became stable due to the even distribution of bandwidth that was set up through a proxy router.